SYSTEMIC ROOTS OF CORRUPTION ─ Corruption and its Perception: Reality vs. Appearance ─ - Madžar, Ljubomir (International Journal of Economic Practice and Policy, 2015)
Serbia is widely believed to be a country flooded with corruption. The question naturally arises as to what might be the causes of this unwelcome phenomenon. The basic stand extensively elaborated in this text is that the causes of the corruption are institutional, i.e. systemic. Without recourse to the systemic causes, the alternative would be that corruption arises from some special anthropological traits of this people. Upon rejecting such an explanation of corruptive practices, the institutional roots are further elaborated. Economic and other policies can also be conducive to corruption, but they are made in an environment structured in the spirit of public choice – policies themselves are motivated by the systemic peculiarities – so that the ultimate determinants are again to be sought in the institutional order of the given society. It might appear at first sight that corruption should be easy to eliminate, as institutions are man-made and not an unchangeable given coming from nature or some uncontrollable entity. However, institutional development is constrained by many factors – knowledge, competent people, information systems, real resources, and financial means – and it is argued that it can be as painful, uncertain, costly and slow as the economic development itself. The complexity of the corruption as an economic, social and even ethical phenomenon is demonstrated by the multiplicity of its definitions and by the conspicuous succession of alternative definitions in time. The problems of measurement are elaborated to some length. Corruption is illegal and therefore, unlike most economic aggregates, cannot be measured directly; it is the perception of the corruption rather than the corruption itself that is being measured in widely cited national and international surveys. The respondents are not centered exclusively at revealing the truth, but are subject to a wide variety of motivations. Some of them are motivated to overstate the extent of corruption, while others are interested in underestimating it. It seems that those bent on overstating it prevail most of the time. As a result, the picture is blurred and uncertain. The multiplicity and disturbing scope of consequences of corruption call for persistent activity aimed at its containing and, where possible, eliminating. As an activity running counter basic ethical principles, corruption is utterly bad and unacceptable by itself. Furthermore, it grossly distorts the prices of commodities and of the production factors and thus undermines the very functioning of the market. It introduces distortions into the choice of the projects, causes departure of the factor proportions from the optimal combination, shortens time horizons in the various spheres of the decision making, makes it impossible to achieve an efficient allocation of resources at various levels in the economic system, undermines credibility among economic actors and with respect to economic policies and distorts these policies themselves. Apart from any other determinants, corruption introduces the possibility of multiple equilibria into economic systems and, as a rule, makes it impossible for these systems to settle at the Pareto optimal points. A number of unequivocally established theoretical results are revealed next. These are presented according to whether they relate to the exogenous corruption, based on externally given rents, or to the endogenous corruption in which the rents depend on the actions and behavioural patterns of the decision makers. The two sets of the results are contraposed, compared and contrasted. Major contradictory corollaries are set out and the implications of their crosscurrents are drawn. The impact of alternative market structures on corruption is examined and the consequences of varying structures in the market for corruption itself are revealed. Particular reference is ascribed to the alleged superiority of the monopolistic market over the competitive market in the turnover of the corruptive services and the claimed superiority of the corruption over lobbying. These results are demonstrated to stem from the basic stand that corruption is exogenous and is fed from the independently given and fixed amount of rents. Turning this stand around and accepting the notion of endogenous corruption, generated by the market actors, makes it possible to reverse these somewhat bizarre and certainly counterintuitive conclusions.